Penerapan Metode Team Games Tournament (TGT) untuk Meningkatkan Kemampuan Belajar Peserta Didik pada Mata Pelajaran Bahasa Indonesia Materi Teks Argumentasi - Sisilia Wahyu Rully A; Denny Denny (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Education is an important key in the formation of an intelligent nation. The background of this study is the decrease in concentration and inactivity of students in learning Indonesian Language, especially in the hours before the end of learning at school. This Classroom Action Research was carried out in two cycles with the aim of increasing the concentration and learning activity of students in grades XI-10 of SMAN 21 Surabaya through the application of the Teams Games Tournament (TGT) method with the Cooperative Learning model in learning Indonesian Language Argumentation Text material. The techniques used in data collection are observation, interviews, and tests. The results of the study show that the application of this TGT method can increase the concentration and learning activity of participants in grades XI-10 of SMAN 21 Surabaya on the Argumentation Text material. This can be seen from the increase in observations, interviews, and test results. Students' learning activities and critical thinking ability have increased with the percentage of score acquisition in cycle 2 higher than in cycle 2. The Teams Games Tournament (TGT) method with the Cooperative Learning learning model allows students to discuss with each other in learning, and can help each other, so that it can increase the activeness and involvement of students during the learning process. In addition, this method helps learners to develop their thinking and communication skills with other friends.